16 A new hospice-based clinic for Advance Care Planning (ACP) and launch of a region-wide education programme for ACP discussions. (14th March 2023) - Head, Julia; Davies, Elsa; Taylor, Amy; Willis, Derek
Abstract : Background: We have previously demonstrated that timely ACP in patients with frailty and neuropalliative conditions can reduce unwanted hospital admissions and improve end of life in preferred places of care (PPC). 1, 2 A new adult ACP has been launched in Shropshire, Telford and Wrekin (STW) and an ACP clinic has opened at Severn Hospice. Data from the first year of the clinic is presented together with details of ACP training delivered to healthcare colleagues. Methods: Patients in their last 12–18 months of life were referred via the hospice day services team. ACPs were written after several conversations, together with ReSPECT and symptom-specific anticipatory plans. Data on non-A&E attendance, non-elective admissions (NELs) and length of hospital stay (LOS) in the 12 months before ACP were compared to the same data 12 months after ACP. Referral activity, symptom control and PPC at end of life were recorded. Results: 26/35 referrals were accepted for ACP. 19/26 patients needed symptom-specific anticipatory plans and 22/26 needed ReSPECT. 14/26 needed symptom control during ACP and 18/26 were referred to other services. 5 patients died: all avoided hospital admission and died in their PPC. Early analysis of hospital data suggests a 58% reduction in unwanted admissions after ACP. Inpatient stays post ACP were all in line with ACP/ReSPECT. Further data will be presented. Conclusion: Timely ACP can have a significant impact in palliative patients. There was a high level of engagement with patients and relatives together with a reduction in unwanted hospital admissions, greater agency for carers and a positive impact on PPC at the end of life. A programme of education has been established across the region to increase delivery of ACP in different settings. References: BMJ Supportive & Palliative Care Mar 2022;12 (Suppl 2):A46; DOI: 10.1136/spcare-2022-SCPSC.120 BMJ Supportive & Palliative Care Mar 2022;12 (Suppl 2):A51; DOI: 10.1136/spcare-2022-SCPSC.134